Unilateral basal ganglia infarction presenting as sudden onset daytime sleepiness - K. C. D. Mettananda; E. M. T. K. De Saram; M. K. I. I. Wickramasinghe; S. A. S. R. Siriwardana (Sri Lanka College of Internal Medicine, 2024)
Basal ganglia (BG) are involved in motor coordination. BG strokes usually present with problems controlling speech, movements, mood and posture leading to abulia which is a prominent feature. BG stroke presenting with daytime sleepiness is not well reported. We report a 63-year- old Asian woman with hypertension presenting with sudden onset daytime sleepiness due to basal ganglia infarction. This case highlights the importance of considering BG infarction as a differential diagnosis for sudden onset daytime sleepiness.